WHERE IS THE GENDER JUSTICE? ANALYSIS OF NOVIA WIDYASARI’S SEXUAL VIOLENCE CASE FROM AN ISLAMIC FEMINIST PERSPECTIVE - Siti Syamsiyatun; Anindya Arfiani (Aqlam: Journal of Islam and Plurality, 2022)
Abstract: Indonesian Komnas Perempuan (National Commission on Violence against Women) and WHO (World Health Organization) reported that violence against women and children, especially sexual violence, is raising during the COVID-19 pandemic era. Such data triggers the authors to question why sexual violence against them persists, and so difficult to be eliminated? Lots of research and casual observation have been presented, many of which are blaming the victims instead of defending them. This present research aims at contributing in answering above questions by conducting qualitative, literature study using a feminist perspective on particular sexual violence experienced by late Novia Widyasari. In so doing we employ also Foucault’s power relation and misogyny culture. We find there are imbalanced power position and misogynic narratives to blame the victim, and to save the life and career of the perpetrators. The deep and widespread of such practices, i.e. power abuse and misogynic attitudes hinder the effort for the elimination of violence, not only against women, but also against minority groups and the weak in our society, such as children, and disabled people. Keywords: Gender; misogyny; power relation; violence Abstrak: Komnas Perempuan Indonesia (Komnas Perempuan) dan WHO (World Health Organization) melaporkan bahwa kekerasan terhadap perempuan dan anak, khususnya kekerasan seksual, meningkat selama era pandemi COVID-19. Data tersebut memicu penulis untuk mempertanyakan mengapa kekerasan seksual terhadap mereka tetap ada, dan begitu sulit untuk dihilangkan? Banyak penelitian dan observasi telah dilakukan, Sebagian besar diantaranya justru menyalahkan para korban alih-alih membela mereka. Penelitian ini bertujuan untuk memberikan kontribusi dalam menjawab pertanyaan di atas dengan melakukan studi literatur kualitatif dengan menggunakan perspektif feminis tentang kekerasan seksual tertentu yang dialami oleh almarhum Novia Widyasari. Dalam melakukannya kami juga menggunakan hubungan kekuasaan Foucault dan budaya misogini. Kami menemukan ada posisi kekuasaan yang tidak seimbang dan narasi misoginis untuk menyalahkan korban, dan untuk menyelamatkan nyawa dan karir para pelaku. Mendalam dan meluasnya praktek-praktek tersebut, yaitu penyalahgunaan kekuasaan dan sikap misoginis menghambat upaya penghapusan kekerasan, tidak hanya terhadap perempuan, tetapi juga terhadap kelompok minoritas dan lemah dalam masyarakat kita, seperti anak-anak, dan orang cacat.Kata Kunci: Gender; misogyny; power relation; violence